2004
DOI: 10.1002/jmv.20275
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of intralesional and intravenous cidofovir in association with indole‐3‐carbinol in an 8‐year‐old girl with pulmonary papillomatosis

Abstract: We report the history of an 8-year-old girl who was treated for suspected lung lesions of respiratory papillomatosis with Indole-3-Carbinol, local and intravenous injections of Cidofovir for 27 months. This is the first report where a complete cure of the lung lesions occurred in a child, and was sustained for at least 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…One of these patients developed a bronchial squamous cell carcinoma and died [127]. Two cases were given prolonged follow-up and experienced persistent improvement; the first one [32] had a follow-up of 18 months; the other one [33], treated at an early stage of the lung disease and with mild involvement in one lobe, is still doing well after more than two years and still on treatment [128]. One case [39] had not improved with intravenous Cidofovir, but improvement was seen when the medication was given via nebulization; this patient is still treated and the improvement persisting [129].…”
Section: Treatment Specific To Lung Involvement In Rrpmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these patients developed a bronchial squamous cell carcinoma and died [127]. Two cases were given prolonged follow-up and experienced persistent improvement; the first one [32] had a follow-up of 18 months; the other one [33], treated at an early stage of the lung disease and with mild involvement in one lobe, is still doing well after more than two years and still on treatment [128]. One case [39] had not improved with intravenous Cidofovir, but improvement was seen when the medication was given via nebulization; this patient is still treated and the improvement persisting [129].…”
Section: Treatment Specific To Lung Involvement In Rrpmentioning
confidence: 99%
“…Details of treatment and outcomes are given in Table 7. Significant improvement was initially reported in three cases [22,32,33]. One of these patients developed a bronchial squamous cell carcinoma and died [127].…”
Section: Treatment Specific To Lung Involvement In Rrpmentioning
confidence: 99%
“…Indole-3-carbinol ( 223 , I3C), a naturally occurring compound found in cruciferous vegetables, such as broccoli and brussel sprouts, is well known for its anticancer and chemopreventive activity in vitro and in vivo [187,188] . It has undergone several clinical trials with promising results [189][190][191] . Although the mechanism by which I3C exerts its anticancer and chemopreventive activity is very complicated and has not been fully elucidated [192] , recent studies indicated that it inhibited activation of Akt and induced apoptosis in MDA MB468 breast, LNCaP prostate and PC3 prostate human cancer cells [193][194][195] .…”
Section: Other Inhibitors Of Akt Activationmentioning
confidence: 99%
“…22 Systemic cidofovir has also been tried but reports are few and anecdotal. 23 Other antivirals Ribavirin is a broad spectrum antiviral which has been used both as an aerosol and systemically. Evidence is anecdotal and it is not widely used.…”
Section: Intralesional Cidofovirmentioning
confidence: 99%